Natural killer T cells in families of patients with systemic lupus erythematosus: Their possible role in regulation of IGG production - Green, Matthew R. J.; Kennell, Amy S. M.; Larche, Maggie J.; Seifert, Martin H.; Isenberg, David A.; Salaman, Myer R. (Arthritis and rheumatism, 2007)
Objective To determine whether there is a link between the frequency of natural killer T (NKT) cells and high levels of IgG in patients with systemic lupus erythematosus (SLE) and their relatives. Methods Blood samples were obtained from patients with SLE, their first‐degree relatives, patients with rheumatoid arthritis (RA), and healthy control subjects. The frequency of NKT cells (defined as CD56+ T cells) was expressed as a percentage of total blood lymphocytes. Plasma levels of total IgG and IgM, and IgG antibodies to double‐stranded DNA (dsDNA) were determined. Results The frequency of NKT cells was lower in patients with SLE than in control subjects. No such decrease was observed in the relatives of patients with SLE or in patients with RA. High levels of IgG were observed in both patients with SLE and their relatives, while low levels of IgM were observed in these same groups. In relatives of patients with SLE, an inverse correlation between the frequency of NKT cells and IgG levels was observed. Moreover, raised levels of IgG in patients with SLE and their relatives and high levels of IgG anti‐dsDNA in patients were associated with low frequencies of NKT cells. Conclusion These results suggest that NKT cells have an important role in the regulation of IgG production, although NKT cells with invariant T cell receptors may not necessarily be involved. NKT cells in the setting of SLE could lack the cytokine stimulus from NK or other cells that is needed to exert control on IgG production. Enhancement of NKT cell activity may provide a novel basis for therapy in SLE.